OXYGEN CONSUMPTION UNDER COPPER AND ZINC STRESS IN PERNA VIRIDIS - PRABHUDEVA, K N; MENON, N R (Fishery Technology, 2017)
The rate of oxygen consumption by Perna viridis pre-exposed to copper and zinc was studied.Those test induviduals pre-exposed to various zinc concentrations showed variability in Oxygen consumption irrespective of concentrations and pre exposure period. while those animals pre-exposed to various copper concentrations regesterd decrease in oxygen consumption at concentrations above 0.06 p.p.m. copper pre- exposure to concentrations below 0.02 p.p.m. copper did not result in any cleare cu change in the rate of oxygen consumption.